Florida 4-H Secretary Record Book: 4H-GCR-01/4H011, rev. 10/2018 - Hensley, Sarah Thomas; Ellison, Stacey (EDIS, 2019)
The Florida 4-H Secretary record book will provide the club secretary with an official outline for tracking all club records. This 30-page book serves as a guide and should be completed annually by the 4-H club secretary. This major revision was written by Sarah Thomas Hensley and Stacey Ellison and published by the UF/IFAS Extension 4-H Youth Development program. http://edis.ifas.ufl.edu/4h011